PENGARUH DIVERSITAS DEWAN DIREKSI DAN KOMISARIS TERHADAP RASIO LEVERAGE PERUSAHAAN MANUFAKTUR YANG LISTING DI BEI PERIODE 2013 - Zakia, Norma; Subagyo, Subagyo; Zen, Fadia (IQTISHODUNA, 2015)
The purpose of this study is to determine the effect of board of directors and commissioner diversitieson leverage ratio. The study population includes all manufacturing companies listed on Indonesia StockExchange in the period of 2013. Samples were taken from 63 manufacturing companies listed on IndonesiaStock Exchange in the period of 2013 with a purposive sampling technique. The analysis technique used wasmultiple linear regressions. The results of this study show that the board of directors and commissioners donot significantly influence the leverage ratio.